Light coherence time modifies color perception of living beings. (2017) - Dellieu, Louis; Cael, Garin; Louette, Michel; Herman, Aline; Deparis, Olivier; Sarrazin, Michael
Abstract: The coloration of objects is commonly understood as the result of three contributions. The first one is the reflectance spectrum which describes the intrinsic light scattering properties of the object and is usually well characterized in the context of natural photonic structures. The second one is the response time of the photodetector which is the human eye as far as color perception of objects is concerned. The third one, which is the focus of the present study, arises from the temporal coherence properties of the incident light. The impact of this last contribution is usually neglected in numerical simulations of photonic structures. Hereafter, we show theoretically how the finite coherence time of the illumination source modifies the color perception of the object by human eyes. As an illustration, we study the human perception of colors of the African Beautiful Sunbird Cinnyris pulchellus .